Protective Effect of DHQ-11 against Hypoxia-induced Vasorelaxation - Zaripov, Abdisalim Abdikarimovich; Jumayev, Inoyat Zulfiqorovich; Usmanov, Pulat Bekmuratovich; Mirzayeva, Yulduzkhon Takhijanovna; Esimbetov, Adilbay Tlepovich; Rustamov, Shavkat Yusubovich; Boboev, Sadriddin Nurillo Ugli; Ibragimov, Eldor Bakhtiyor Ugli; Qurbonova, Shakhnoza Bakhtiyorovna; Zhurakulov, Sherzod Niyatqobulovich (Trends in Sciences, 2024)
Hypoxia, or the lack of oxygen, has multiple impacts on the vascular system. The major molecular sensors for hypoxia at the cellular level are hypoxia inducible factor and heme oxygenase. Hypoxia also acts on the vasculature directly conveying its damaging effects through disruption of the control of vascular tone, particularly in the coronary circulation, enhancement of inﬂammatory responses and activation of coagulation pathways. These effects could be particularly detrimental under pathological conditions such as obstructive sleep apnea and other breathing disorders. Introduction: The effect of conjugate 2-(3,4-Dihydroxyphenyl)-6-[1-(2’-bromo-3’,4’-dimethoxyphenyl)-6,7-dimethoxy-3,4-dihydroisoquinolin-2(1H )-yl]methyl-3,5,7-trihydroxychroman-4-one (DHQ-11) on hypoxia-induced vasorelaxation was investigated in rat aortic rings using standard organ bath techniques. Materials and methods: Hypoxia was stimulated by a superfusion of aortic rings with a glucose-free Krebs solution bubbled with 95 % N2/5 % CO2. The effect of conjugate DHQ-11 was assessed after a 60- min period of hypoxia on aortic rings precontracted with 50 mm KCl or 1µM phenylephrine (PE). The conjugate DHQ-11 significantly attenuated hypoxia-induced vasorelaxation in the endothelium-intact aortic rings precontracted with KCl or PE in a concentration-dependent manner. Results and discussion: This effect of conjugate DHQ-11 was more potent in aortic rings precontracted with PE than those with KCl where it maximally reduced hypoxia-induced vasorelaxation from 44.7 ± 3.7 to 5.4 ± 3.7 and 33.9 ± 3.4 to 10.8 ± 4.2 %, respectively. The removal of the endothelium attenuated the effect of conjugate DHQ-11 on hypoxia-induced vasorelaxation. Similarly, pretreatment of endothelium-intact aortic rings with L-NAME and methylene blue also attenuated the effect of conjugate DHQ-11 on hypoxia-induced vasorelaxation. Furthermore, the blockade of the ATP-sensitive KATP channel with glibenclamide and the calcium-activated large conductance BKCa channel with TEA also significantly attenuated the effect of conjugate DHQ-11 on hypoxia-induced vasorelaxation. Collectively, these results indicated that conjugate DHQ-11 attenuated the hypoxia-induced vasorelaxation suggesting that it alleviated the oxidative damage of vasculature. Conclusions: This effect of conjugate DHQ-11 possible is mediated through several mechanisms including the blockage of the extracellular Ca2+ entry via the voltage-dependent and receptor-operative Ca2+ channels, as well as inhibition of sarcoplasmic reticulum Ca2+ release via the inositol triphosphate pathway. In addition, endothelium and NO/sGC/cGMP/PKG pathway, as well as KATP and BKCa channels most likely participate in protection by conjugate DHQ-11 against hypoxia-induced vasorelaxation. HIGHLIGHTS Conjugate DHQ-11 (1-(2´-bromo-4´,5´-dimethoxyphenyl)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline alkaloid and Dihydroquercetin flavonoid) was formed by chemical connection. Conjugate DHQ-11 exerts potent vasorelaxant and vasoprotective effects on KCl- and PE-induced contractions in rat aortic vascular SMCs. The vasoprotective effect of conjugate DHQ-11 effectively protects blood vessels from hypoxia-induced damage through the modification of the function of Ca2+L channels and IP3 cascade, as well as the activation of NOS, NO/sGC/cGMP/PKG signaling pathways, KATP and KCa GRAPHICAL ABSTRACT